2021
DOI: 10.1038/s41467-021-22840-7
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation reduces rainfall and agricultural revenues in the Brazilian Amazon

Abstract: It has been suggested that rainfall in the Amazon decreases if forest loss exceeds some threshold, but the specific value of this threshold remains uncertain. Here, we investigate the relationship between historical deforestation and rainfall at different geographical scales across the Southern Brazilian Amazon (SBA). We also assess impacts of deforestation policy scenarios on the region’s agriculture. Forest loss of up to 55–60% within 28 km grid cells enhances rainfall, but further deforestation reduces rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(131 citation statements)
references
References 46 publications
5
117
0
9
Order By: Relevance
“…As already mentioned, this region also is characterized by strong seasonal variability due to the South American Monsoon System, which represents one of the most prominent summertime climate patterns in South America [45]. This region's native vegetation corresponds to the Open Ombrophilous Forest type, with a canopy height of around 20-25 m and emerging trees reaching 30-35 m, dominated by valuable timber species [40][41][42][43][44][45][46][47][48][49][50][51][52]. The annual average temperature in this region is 26 • C, and the average annual rainfall is 2438 mm, with well-defined dry and moderate water deficit conditions during the winter months of June and August (Figure 1C).…”
Section: Study Areamentioning
confidence: 93%
See 1 more Smart Citation
“…As already mentioned, this region also is characterized by strong seasonal variability due to the South American Monsoon System, which represents one of the most prominent summertime climate patterns in South America [45]. This region's native vegetation corresponds to the Open Ombrophilous Forest type, with a canopy height of around 20-25 m and emerging trees reaching 30-35 m, dominated by valuable timber species [40][41][42][43][44][45][46][47][48][49][50][51][52]. The annual average temperature in this region is 26 • C, and the average annual rainfall is 2438 mm, with well-defined dry and moderate water deficit conditions during the winter months of June and August (Figure 1C).…”
Section: Study Areamentioning
confidence: 93%
“…The closest city is Itapuã do Oeste, The southwestern Brazilian Amazon, and especially the state of Rondônia, has been facing substantial forest losses since the late 1980s due to intense human activities across its territory's land surface [39]. Our studied site is located at the heart of this accelerated land cover change area, which, after three decades of increased deforestation, fires, and forest fragmentation, has been experiencing dramatic changes in seasonal precipitation chemistry [40] and regional hydroclimate shifts [41,42], which can potentially impact the livelihoods of people in the state [43].…”
Section: Study Areamentioning
confidence: 99%
“…This area is at high-risk of deforestation as a direct result of weakened governance; cattle ranching thrives here as a driver of deforestation (Margulis 2004). Should these conditions continue, Leite-Filho et al (2021) estimate that the fringe region of the Brazilian Amazon will have lost more than half of its forested area by 2050; whilst Campbell (2008) notes that forced labour is a key method applied to clear this land. These locations are easy to access; roads penetrate the forests, and an explosion in illegal logging practices have been reported as having ravaged the region (Lawson et al 2014;Dummett et al 2021).…”
Section: The Case Of Cattle In Brazilmentioning
confidence: 99%
“…For example, deforestation -contributed in part by the continued subjection of individuals to modern slavery -leads to losses in the agricultural sector, particularly through the reduction of rainfall (Leite-Filho et al 2021). Such implications are associated with agricultural losses and the displacement of communities.…”
Section: The Case Of Cattle In Brazilmentioning
confidence: 99%
“…Other studies also revealed that global forest cover has decreased from 4128 to 3999 Mha during 1990-2015 [6], and 420 Mha of the global forest area has been lost due to deforestation during 1990-2020 [7]. Such deforestations have a serious effect on rainfall distribution and would alter the structure and functions of the forest [8,9]. Understanding rainfall variation with respect to changes and fluctuations in the forested landscape is important [10,11], as it can be a useful input to models of ecological and environmental processes at local, regional and global scales.…”
Section: Introductionmentioning
confidence: 99%